2019
DOI: 10.3390/ma12233927
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical High-Temperature Properties and Damage Behavior of Coarse-Grained Alumina Refractory Metal Composites

Abstract: The present study provides the mechanical properties of a new generation of refractory composites based on coarse-grained Al2O3 ceramic and the refractory metals Nb and Ta. The materials were manufactured by refractory castable technology and subsequently sintered at 1600 °C for 4 h. The mechanical properties and the damage behavior of the coarse-grained refractory composites were investigated at high temperatures between 1300 and 1500 °C. The compressive strength is given as a function of temperature for mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 44 publications
1
34
0
Order By: Relevance
“…The impurity phase NbO identified by EDS measurements was frequently present within niobium particles as it is shown in Figure 2b. Ternary oxide formation, e.g., of AlNbO 4 as reported in [19], at the interface alumina/niobium oxide was not detected by SEM/EDS. Furthermore, the niobium material showed only a less pronounced tendency for surface diffusion along the alumina grains in comparison to the previous case of a mixture with a tabular alumina material [18].…”
Section: Fine-grained Compositementioning
confidence: 68%
See 2 more Smart Citations
“…The impurity phase NbO identified by EDS measurements was frequently present within niobium particles as it is shown in Figure 2b. Ternary oxide formation, e.g., of AlNbO 4 as reported in [19], at the interface alumina/niobium oxide was not detected by SEM/EDS. Furthermore, the niobium material showed only a less pronounced tendency for surface diffusion along the alumina grains in comparison to the previous case of a mixture with a tabular alumina material [18].…”
Section: Fine-grained Compositementioning
confidence: 68%
“…The concept of coarse-grained refractory composites based on tantalum-alumina and niobium-alumina was recently introduced [18] combining the fields of powder metallurgy and castable technology. Shrinkage values of ≈1% and good mechanical properties at ambient temperature as well as in the temperature range of 1300-1500 °C [19] were obtained. Low shrinkage on sintering causes also low values of residual stresses in the refractory ceramic, which enables one to fabricate large refractory components.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Refractory metals with a melting point above 2000 C, namely Nb and Ta, were chosen and combined with alumina. Composites showed plastic deformation behavior between 1300 C and 1500 C [ 6 ]. The shrinkage of the coarse-grained refractory composites was clearly reduced in comparison to fine-grained materials, with the additional benefit of low residual stresses.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Lessing et al [ 10 ] found that the pure material has worse mechanical properties than alumina doped with transition metal ions. Weidner et al [ 11 ] studied the high temperature mechanical properties of alumina-based composites reinforced with a 11 or 21 vol.% of refractory metal Ta and Nb, respectively. These materials did not fail in a completely brittle manner during compression tests between 1300–1500 °C.…”
Section: Introductionmentioning
confidence: 99%